Basic grammar in many voices - Silva, Marilyn Neva (Lincolnwood, Ill. NTC Pub. Group, 1998)
Explains the basics of English grammar, including parts of speech, sentence structure, modifiers, clauses, idea coordination, and punctuation, and provides practice exercises.
Keywords: English language -- Grammar; English language -- Grammar -- Problems, exercises, etc